Manejo integrado (MI) de Bemisia Tabaci en cultivos hortícolas, cantón Babahoyo, provincia Los Ríos - Tenorio Ortiz, Rosa Andreina (2019)
The present investigation on the Integrated Management of whiteflies (Bemisia tabaci) as virus vector pests in various vegetable crops, aims to gather information on the biology and behavior of the whitefly that have the ability to transmit viruses to plants and in order to describe the strategies that have proven to be more effective and sustainable for the Integrated Management of this species. The information provided in this research is the result of experiences and research work carried out by researchers and agricultural extensionists from all over the world where they present themselves with Bemisia tabaci and the way they have managed their Integrated Management. And primarily, results of research conducted in the province of Los Ríos are focused. All this work in order to provide a contribution to the area of Organic Agriculture of the Faculty of Agricultural Sciences, where students of the Faculty of Agricultural Sciences conduct their training and experimental research practices